ChemInform Abstract: A New Synthesis of Chiral Oxazolidinones from the Amino Acid L‐Serine. Issue 18 (6th May 2014) - Nogueira, Thais C. M.; Pinheiro, Alessandra C.; Kaiser, Carlos R.; Wardell, James L.; Wardell, Solange M. S. V.; de Souza, Marcus V. N.
Abstract The synthesis assumes N‐Cbz protection of L‐serine and is preceded by N‐methylation of the hydrazide.